Respuesta :

Let's see here... well, since the first letter in the ratio is from the first triangle, then, the first one in the equal ratio is going to have to be that as well, and the ratio of c:a wouldn't work, since c was already used. By process of elimination, it's gotta be b:q.

we know that

If triangle ABC is similar to triangle PQR

then

the corresponding sides are proportional

so

[tex]\frac{AC}{PR}= \frac{AB}{PQ}= \frac{BC}{QR}[/tex]

substitute the values

[tex]\frac{b}{q}= \frac{c}{r}= \frac{a}{p}[/tex]

[tex]\frac{c}{r}=\frac{b}{q}[/tex]

[tex]\frac{c}{r}=\frac{a}{p}[/tex]

therefore

the answer is the option

[tex]b:q[/tex]